PEMBUATAN PETA SITUASI DUSUN KALICANGAK DAN DUSUN KALITURI DESA BELUK KECAMATAN BAYAT KABUPATEN KLATEN PROPINSI JAWA TENGAH - , CHRIST KURNIAWAN A ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The Final report titled \"SITUATION MAP PRODUCTION OF KALICANGAK AND KALITURI HAMLET BELUK VILLAGE BAYAT SUB DISTRICT KLATEN DISTRICT CENTRAL JAVA PROVINCE\" describes the measurement and mapping of terrestrial to obtain spatial data. Spatial data in the form of planimetric detail and high detail then presented in the form of a map. The result is a situation map scale 1: 500 KALICANGAK AND KALITURI HAMLET BELUK VILLAGE BAYAT SUB DISTRICT KLATEN DISTRICT CENTRAL JAVA PROVINCE. Map this situation using WGS'84 datum (World Geodetic System) and projection UTM (Universal Trasverse Mercator). Map of the situation has been tested with a test implementation map. Test the truth of the map reaches the level of 75% for the test range, 70% to test the state of the field, and 60% for higher test point. From the test results map the data do not meet the tolerance, then do repairs and editing so that the map can meet tolerances.